Applications of pullulan active packaging incorporated with green synthesized curcumin (C-AgNPs) and pullulan (P-AgNPs) mediated silver nanoparticles on quality of broiler meat - Muhammad, Jamshed (2021)
Active meat packaging is an innovation to maintain the quality, sensory characteristics, safety and shelf life of meat containing the “active” component as an antibacterial or antioxidant substance. Application of ‘nanoparticles’, have been reported in last decade. Green silver nanoparticles (AgNPs), synthesis by various physical and chemical routes, have been adopted by food industry as antimicrobial substances. The oxidative rancidity of meat can cause the formation of hazardous chemical compounds without the synthetic anti-oxidants (butylated hydroxyl-toluene, Butylated hydroxylanisole, propyl gallate). Moreover, curcumin (C-AgNPs) and pullulan mediated silver nanoparticles (P-AgNPs) have, limitedly, been reported as green anti-oxidant substance for meat preservation. Similarly, pullulan active packaging, incorporated with CAgNPs and P-AgNPs, are not being reported as active meat packaging so far. Based on these facts, the current study was planned to obtain green C-AgNPs and P-AgNPs from chemical and physical methods. The impact of C-AgNPs and P-AgNPs incorporation on physico-chemical characteristics of pullulan active packaging along with oxidative stability and organolaptic properties of broiler meat treated with pullulan active packaging were also examined. The synthesis of C-AgNPs was achieved by reduction of silver nitrate (AgNO3) in an alkaline medium. The formation of C-AgNPs was evaluated by the dark colour of the colloidal solutions and UV-vis spectra, with 445 nm as the maximum. The size of the crystalline nanoparticles, recorded as 12.6 ± 3.8 nm, was confirmed by HRTEM, while the face-centred cubic (fcc) crystallographic structure was confirmed by powder X-ray diffraction (PXRD). The synthesis of PAgNPs was achieved through ultraviolet (UV) irradiation for 96 h. P-AgNPs were formed after 24h of UV-irradiation time and expressed spectra maxima as 415 nm, after 96 h, in UV-vis spectroscopy. The crystallographic structure was “face centred cubic (fcc)”as confirmed by PXRD. HRTEM analysis proved that P-AgNPs were covered with a thin layer of pullulan, with a mean crystalline size of 6.02 ± 2.37. Pullulan edible films were prepared by mixing glycerol and xanthan gum in pullulan (5% w/v) aqueous solution. The solution was homogenized at 80 ± 1°C. C-AgNPs and P-AgNPs were incorporated at a rate of 2% v/v in pullulan edible film to prepare four active meat packaging i.e. control (PF-CTRL); with C-AgNPs (PF-C-AgNPs); with PAgNPs (PF-P-AgNPs); and with mixed AgNPs (PF-M-AgNPs) as active meat packaging. Significant differences (p ≤ 0.05) were observed in chromatography (ΔE), sharpness (L*), green appearance (a*), yellowness (b*), chroma, hue, volume and area of pullulan active packaging incorporated with AgNPs (PF-C-AgNPs; PF-P-AgNPs and PF-M-AgNPs) or without AgNPs (PF-CTRL). For in-vivo anti-oxidant activity, a bi-layer pullulan active packaging (PF-CTRL, PF-C-AgNPs, PF-P-AgNPs and PF-MAgNPs) was applied on clean broiler breast meat (Pectoralis major) and stored at 4°C for 0, 7 and 14 days. Significant differences were observed in pH, drip loss percentages, chromatography (ΔE), lightness (L*), redness (a*), yellowness (b*), chroma, hue, and total expressible fluid percentages of meat samples wrapped into pullulan active packaging from control meat samples (CTRL). The meat samples treated with PF-C-AgNPs active packaging showed highest expressible fluid percentage (63.375 ± 10.53) at day 7 as compared to the controlled (CTRL) meat samples (32.751 ± 7.26), PF-CTRL (43.76 ± 7.19), PF-P-AgNPs (49.714 ± 4.38), and PF-M-AgNPs (49.263 ± 2.365) active packaging. The drip loss percentages for the meat samples treated with PF-C-AgNPs and PF-M-AgNPs was lowest at 7th (0.78 ± 0.128; 0.99 ± 0.119) and 14th day (2.60 ± 0.584; 3.60 ± 0.601) of refrigerated storage. PF-C-AgNPs active packaging exhibited statistically higher antioxidant capacity (ABTS/ DPPH) along with lower MDA contents (mg/ kg of meat) as compared to the other pullulan edible active packaging i.e. PF-CTRL, PF-P-AgNPs and PF-M-AgNPs. It is concluded that PF-C-AgNPs and PF-P-AgNPs active packaging can be adopted as green anti-oxidant alternate to preserve the quality of broiler meat during 14 days of refrigerated storage.